Headache as the sole presenting symptom of cerebral venous sinuses thrombosis: Subgroup analysis of data from the VENOST study - MİDİ, İPEK (KARE PUBL, 2020)
Objectives: Headache is the most common complaint in cerebral venous sinus thrombosis (CVST) and it may sometimes be the only symptom in these patients. This retrospective and prospective study was an investigation of any differences in terms of clinical risk factors, radiological findings, or prognosis in patients with CVST who presented with isolated headache (IH) and cases with other concomitant findings (non-isolated headache [NIH]). Methods: A total of 1144 patients from a multicenter study of cerebral venous sinus thrombosis ( VENOST study) were enrolled in this research. The demographic, biochemical, clinical, and radiological aspects of 287 IH cases and 857 NIH cases were compared. Results: There were twice as many women as men in the study group. In the IH group, when gender distribution was evaluated by age group, no statistically significant difference was found. The onset of headache was frequently subacute and chronic in the IH group, but an acute onset was more common in the NIH group. Other neurological findings were observed in 29% of the IH group during follow-up. A previous history of deep, cerebral, or other venous thromboembolism was less common in the IH group than in the NIH group. Transverse sinus involvement was greater in the IH group, whereas sagittal sinus involvement was greater in the NIH group. The presence of a plasminogen activator inhibitor (PAI) mutation was significantly greater in the IH group. Conclusion: IH and CVST should be kept in mind if a patient has subacute or chronic headache. PAI, which has an important role in thrombolytic events, may be a risk factor in CVST. Detailed hematological investigations should be considered. Additional studies are needed.
Keywords: Cerebral venous sinus thrombosis; cerebrovascular disease; headache